2019
DOI: 10.1002/jlb.4a0518-189r
|View full text |Cite
|
Sign up to set email alerts
|

Diminished secretion and function of IL-29 is associated with impaired IFN-α response of neonatal plasmacytoid dendritic cells

Abstract: Plasmacytoid dendritic cells (pDCs) are key players in the antiviral immune response and type III IFNs such as IL‐29 appear to play a pivotal role in pDC function. Pronounced susceptibility to viral infections in neonates is partly resulting from diminished antiviral immune mechanisms. Accordingly, the aim of the present study was to investigate the impact of IL‐29 in the altered immune response of neonatal pDCs. PBMCs of adult and term newborns were stimulated with CpG‐ODN2216 in the presence or absence of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Costimulation with interleukin-29 and IFN-resulted in a dramatic upregulation of CD80, CD83, and ICOS-L expression in pDCs, the primary source of IFN-. As shown by these results, IL-29 has the potential to control the activation and immunostimulatory capacity of pDCs via modulating the expression of costimulatory molecules (10) .…”
Section: Essential Function Of Interleukin-29 In Innate Immunitymentioning
confidence: 86%
“…Costimulation with interleukin-29 and IFN-resulted in a dramatic upregulation of CD80, CD83, and ICOS-L expression in pDCs, the primary source of IFN-. As shown by these results, IL-29 has the potential to control the activation and immunostimulatory capacity of pDCs via modulating the expression of costimulatory molecules (10) .…”
Section: Essential Function Of Interleukin-29 In Innate Immunitymentioning
confidence: 86%
“…pDCs are the main secretor of IFN‐α . IL‐29 combined with cytosine‐phosphate‐guanosine oligodeoxynucleotides (CpG‐ODN) or GPG2216 stimulation on pDCs promoted INF‐α secretion . These data reflected that IL‐29 is able to regulate costimulatory molecules expression and may play a role in activation and immunostimulatory potential of pDCs.…”
Section: Biologic Functions Of Il‐29mentioning
confidence: 87%
“…26 IL-29 combined with cytosine-phosphate-guanosine oligodeoxynucleotides (CpG-ODN) or GPG2216 stimulation on pDCs promoted INF-α secretion. 26,27 These data reflected that IL-29 is able to regulate costimulatory molecules expression and may play a role in activation and immunostimulatory potential of pDCs. 16 These findings suggested that IL-29 had an ability to regulate cytokine release and induce mast cell infiltration.…”
Section: Significant Role Of Il-29 In Innate Immunitymentioning
confidence: 91%
See 1 more Smart Citation
“…IL-28A, IL-28B, and IL-29 form the subfamily of IL-20 4 . IL-29 exhibits multiple biological activities including immune regulatory activity, anti-viral 5 , obesity-induced inflammation 6 , and anti-tumor properties 7 . IL-29 has been shown to have anti-tumor effects on many human cancer cells such as melanoma 8 , neuroendocrine cancer 9 , colorectal cancer 10 , and glioblastoma 11 .…”
Section: Introductionmentioning
confidence: 99%